EFEKTIVITAS MEDIA ISOMETRIC DRAWING BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN KUBUS DAN BALOK KELAS VI SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Fani Hamzany; Masniladevi; Mukta Hildatul Berby (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Geometry learning on cube and rectangular prism topics in elementary schools still faces several challenges, particularly students’ difficulties in visualizing three-dimensional objects and understanding the relationships among geometric elements. These challenges are influenced by the limited use of visual learning media and the dominance of instructional approaches that do not fully engage students in constructing conceptual understanding. This study aims to analyze the effectiveness of integrating isometric drawing media with the Problem Based Learning (PBL) model in supporting students’ understanding of cube and rectangular prism concepts in elementary schools. The research employed the Systematic Literature Review (SLR) method by analyzing 20 scientific articles related to geometry learning, visual media, isometric drawing, spatial reasoning abilities, and the implementation of PBL in elementary education. The article selection process consisted of identification, screening, eligibility assessment, and inclusion based on predetermined criteria. The collected data were analyzed using descriptive qualitative analysis through thematic synthesis to identify patterns and main findings from the selected studies. The results indicate that isometric drawing media helps students visualize three-dimensional objects, understand geometric concepts, and improve spatial reasoning abilities. Furthermore, the implementation of PBL contributes to enhancing conceptual understanding, critical thinking skills, problem-solving abilities, and students’ active participation. The integration of isometric drawing media and PBL provides a potential instructional alternative for developing contextual, visual, and student-centered geometry learning in elementary schools. ABSTRAK Pembelajaran geometri pada materi kubus dan balok di sekolah dasar masih menghadapi berbagai kendala, terutama berkaitan dengan rendahnya kemampuan siswa dalam memvisualisasikan objek tiga dimensi dan memahami hubungan antarunsur bangun ruang. Kondisi tersebut dipengaruhi oleh keterbatasan penggunaan media pembelajaran visual serta dominannya pendekatan pembelajaran yang belum sepenuhnya melibatkan siswa secara aktif dalam membangun pemahaman konsep. Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan media isometric drawing berbasis Problem Based Learning (PBL) dalam mendukung pemahaman konsep kubus dan balok pada siswa sekolah dasar. Metode penelitian yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis 20 artikel ilmiah yang berkaitan dengan pembelajaran geometri, media visual, isometric drawing, kemampuan penalaran spasial, dan penerapan model PBL pada jenjang sekolah dasar. Proses seleksi artikel dilakukan melalui tahapan identifikasi, penyaringan (screening), penilaian kelayakan (eligibility), dan inklusi berdasarkan kriteria yang telah ditetapkan. Data dianalisis menggunakan teknik deskriptif kualitatif melalui sintesis tematik untuk mengidentifikasi pola dan temuan utama dari berbagai penelitian. Hasil kajian menunjukkan bahwa penggunaan media isometric drawing mampu membantu siswa memvisualisasikan objek tiga dimensi, memahami konsep bangun ruang, serta meningkatkan kemampuan penalaran spasial. Selain itu, penerapan PBL berkontribusi terhadap peningkatan pemahaman konsep, kemampuan berpikir kritis, pemecahan masalah, dan keterlibatan aktif siswa. Integrasi isometric drawing dengan model PBL menjadi alternatif pembelajaran yang potensial dalam menciptakan pembelajaran geometri yang lebih kontekstual, visual, dan berpusat pada siswa.